ANALISIS KETIDAKSEIMBANGAN BEBAN GARDU DISTRIBUSI PASANGAN LUAR 20/0,4 KV - Redo Fajri; Dewanto Indra K (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This study analyzes load imbalance in outdoor 20/0.4 kV distribution substations, a crucial issue in the electrical power infrastructure that can reduce system efficiency and affect the asset's health index according to PT PLN (Persero) standards. Unlike previous studies, this research comprehensively calculates the percentage of load imbalance based on field inspection data, classifies it into the substation's health index, and validates the theoretical neutral current calculations with ETAP software simulations. The main objectives of this study are to determine the percentage of load imbalance and the health index grouping after load balancing, and to measure the error value between theoretical calculations and ETAP simulations for the neutral phase current.The results show that the load balancing strategy is effective in reducing the percentage of imbalance in substations that previously had a